A Portable Optical Sensor for Microplastic Detection: Development and Calibration - Maximiliano Campos-López; Ricardo Aguilar-Garay; Dafne E. González-Rodriguez; Verónica I. Mejía-Lopez; Margoth M. Gamboa-Lugo; Vicente Garibay-Febles; Marco A. Reyes-Guzmán; Álvaro Gordillo-Sol; Jorge A. Mendoza-Pérez (Applied Sciences)
Microplastics are ubiquitous in the environment and represent a serious risk to ecosystems and human health. This study describes a prototype sensor designed to detect microplastics by analyzing samples with multiple wavelengths of light. The system uses samples of commercially available microplastics and includes passive low-pass filters to reduce noise for accurate readings. The prototype measures light attenuation and produces color spectra that helps identify microplastics. Its design focuses on precision, electronic control, and optical sensing, making it an affordable option for environmental monitoring. Early experiments demonstrate that the prototype is sensitive and reliable under a variety of conditions. Future improvements may add machine learning and fuzzy logic to increase accuracy and expand its use.